Exploring the distinctions between Startups and small and medium-sized enterprises (SMEs): A comparative analysis - Abdelghani, Bahmed (International journal of economic perspectives, 2024)
This article delves into the nuanced differences between startups and small and medium-sized enterprises (SMEs). While both categories encompass businesses operating at relatively smaller scales, they exhibit distinct characteristics in terms of their organizational structure, growth trajectory, and risk factors. By conducting a comparative analysis, this study aims to elucidate these disparities, providing valuable insights for entrepreneurs, invertors and policymakers.